The evolution of energy efficiency in Switzerland in the period 2000–2016. (15th January 2020) - Bhadbhade, Navdeep; Yilmaz, Selin; Zuberi, Jibran S.; Eichhammer, Wolfgang; Patel, Martin K.
Abstract: Substantial improvement in traditional energy intensity indicator (4.5% p.a.) for Switzerland in the period 2000 to 2016 points towards strong decoupling of economic growth and energy demand. Since the improved energy intensity could be primarily driven by soaring value added, it is necessary to analyse 1) physical energy efficiency (EE) representing the contribution of technical progress to EE improvement and 2) the influence of other drivers of total final energy (TFE) demand. This work evaluates physical energy efficiency (EE) trends in Switzerland at various aggregation levels by applying the ODYSSEE energy efficiency index (ODEX). The ODEX methodology facilitates the estimation of physical (technical) EE trends based on subsector-specific physical activity indicators. Switzerland improved its physical EE by 1.4% p.a. in the period 2000–2016 with household being the fastest and industry being the slowest improving sector. Physical EE improvement was enhanced by structural change but it was partly offset by larger dwellings, more appliances per dwelling and physical activity growth. Although the combined indicator identifies Switzerland as the third best amongst the countries in ODYSEE database, individual sectors in Switzerland still need to increase their rate of EE improvement in order to meet the 2050 targets of Swiss Energy Strategy 2050. Highlights: Switzerland displays Strong decoupling of economic growth and energy consumption. Physical energy efficiency (EE) improved at the rate of 1.4% p.a. in Switzerland. Household sector in Switzerland was fastest to improve its EE (1.7% p.a.). Industry sector in Switzerland was the slowest to improve its EE (1.0% p.a.). A shift toward low energy intensive activities is observed in Switzerland.